A Case Study on Effective Locations for Retail Companies in Padang City - Khatimah, Husnul; Adilla, Firliana; Syahputri, Khoirani; Amelia, Rizka; Murdani, Risya; Juniandayu Putri, Reza (Journal of Multidimensional Management, 2024)
This research explores the influence of location selection strategy on the operational performance of Retail Company 'S' in Padang City, West Sumatra. This study uses a mixed-methods approach that combines quantitative and qualitative data analysis. Quantitative data was obtained from field surveys and literature analysis, while qualitative data was collected through interviews with the company. Retail Company 'S' used the Factor Ranking Method as the main tool in making location decisions. The results show that proximity to markets and suppliers is the main factor in location selection, with operational costs and public perception of the company also being important considerations. The right location selection strategy is proven to improve visibility, accessibility and customer appeal, which significantly contributes to the success of modern retail businesses in Padang City. The findings provide important insights for operations managers in designing effective and efficient location strategies to achieve optimal operational performance.